When imperfect is preferred: the differential effect of aesthetic imperfections on choice of processed and unprocessed foods - Suher, Jacob; Szocs, Courtney; van Ittersum, Koert (Journal of the Academy of Marketing Science, 2021)
AbstractSome companies design processed foods to contain aesthetic imperfections such as non-uniformities in shape, color, or texture. Simultaneously, consumers annually discard millions of pounds of unprocessed, safe-to-eat fruits and vegetables owing to aesthetic imperfections. Why design processed foods with aesthetic imperfections when people discard unprocessed foods because of them? Seven studies, including a choice study at a grocery store and an incentive-compatible study, show that the effect of aesthetic imperfections on consumer preferences depends on whether foods are unprocessed or processed. While imperfections negatively influence preferences for unprocessed foods, they positively influence preferences for processed foods. We attribute this preference shift to consumers making opposing inferences about the human care involved in producing aesthetically imperfect processed and unprocessed foods. Building on research highlighting the positive effects of human presence in production, we thus show that perceived care drives food choice. We discuss implications for product design, retail promotion, and sustainability.